STUDENTS’ PERCEPTIONS OF THEIR REFLECTIVE ESSAY WRITING EXPERIENCE AND TEACHER FEEDBACK COMMENTS - Sharif, Asiah Mohd; Zainuddin, Siti Zaidah (Universitas Pendidikan Indonesia, 2017)
Reflection which encompasses critical and analytical capabilities is a critical 21st century skill for students to develop. To ensure students are equipped with this skill, reflective writing has been identified as a possible tool. Teacher feedback on students’ written output therefore plays a role in developing students’ reflective skills. This study asks two questions: How do students perceive their experience writing reflective essays? What is the nature of the teacher’s feedback comments on students’ reflective essays and how do students perceive them? To answer these questions, nineteen ESL students in an entry-level Medical programme completed a questionnaire concerning their experiences writing reflective essays and perceptions of teacher feedback on these essays. Interviews were conducted with two students to follow-up on questionnaire responses. The content analysis showed that the students believed reflective writing played a small contribution to their language learning. Further investigation into the students’ perspectives of their teachers’ feedback comments suggests that even though the teachers’ feedback was positive, the students also referred to the comments as inadequate and ineffective. Pedagogical implications and suggestions for future research are discussed.